An automated Langmuir probe controller for plasma characterization. (6th July 2016) - Bustos, A; Juarez, A M; de Urquijo, J; Muñoz, M
Abstract: We present the design, construction and test of an automated electronic controller for a Langmuir plasma probe. The novel aspect of this system lies in the isolation of the high voltage present in the discharge from the grounded reference of the controller. This controller detects currents over the range from ±1 μ A to ±50 mA, using dynamic and automated switching of a transresistance amplifier. This automated Langmuir probe (LP) system has been successfully tested in a glow discharge in argon at 0.8 and 10 Torr.